Lenvatinib promotes hepatocellular carcinoma pyroptosis by regulating GSDME palmitoylation - Yuan Yuan; Mu-Ru Wang; Yang Ding; Ya Lin; Ting-Ting Xu; Xing-Xing He; Pei-Yuan Li (Cancer Biology & Therapy, 2025)
Lenvatinib, as a multi-kinase inhibitor, has been approved as a first-line drug for patients with advanced hepatocellular carcinoma (HCC). Gasdermin E (GSDME)-mediated pyroptosis, a form of programmed cell death, can be induced by chemotherapy drugs or certain kinase inhibitors. However, the role of Lenvatinib in inducing pyroptosis in HCC warrants further investigation. Phase contrast microscopy, LDH assays, and gain- and loss-of-function strategies were used to evaluate Lenvatinib-induced pyroptosis in HCC cells. GSDME palmitoylation was assessed via the acyl-biotin exchange method. In vivo, a subcutaneous HCC xenograft model in nude mice were established to assess the effects of interfering with GSDME on the sensitivity of HCC to Lenvatinib. Lenvatinib induced pyroptosis in HCC cells in a dose- and time-dependent manner. Additionally, Lenvatinib promoted GSDME cleavage, with upregulation of GSDME enhancing pyroptosis and downregulation reducing this effect. The ABE method revealed that GSDME is palmitoylated, and Lenvatinib increased its palmitoylation, promoting plasma membrane localization and enhancing protein stability. Inhibition of GSDME palmitoylation by 2-BP blocked Lenvatinib-induced pyroptosis. In vivo, upregulation of GSDME increased HCC sensitivity to Lenvatinib and inhibited tumor growth. Lenvatinib induces pyroptosis in HCC by promoting the palmitoylation of GSDME, enhancing its localization to the plasma membrane and increasing its protein stability. Interfering with GSDME, both in vitro and in vivo, affects Lenvatinib-induced pyroptosis, thereby altering the therapeutic sensitivity of HCC to Lenvatinib. Targeting GSDME palmitoylation represents a potential therapeutic strategy for HCC, as it enhances Lenvatinib-induced pyroptosis and improves the therapeutic response.